Self-Medication in Pregnancy and Associated Psychopathological Symptoms of Antenatal Nigerian Women - Bello, Ibukunoluwa (Psychology, 2020)
The physical and psychological health challenges of Self-Medication (SM) for a pregnant woman and the unborn child spotlights it as an emergency. This unwraps a gap in epidemiological studies on SM and associated psychopathological symptoms among Nigerian pregnant women. This study examines the predictive influence of self-medication with Over The Counter (OTC)drugs on manifested psychopathological symptoms among pregnant women attending antenatal clinic in State Specialist Hospital, Osogbo, Osun State, southwestern Nigeria. Purposively selected 277 pregnant women ( x age =29.33; SD = 4.77) participated in the study. The participants responded to the Substance Abuse Prevalence Inventory, Self-Medication Test (SMT), and Awaritefe Psychological Index (API). Findings reveal a low prevalence of psychoactive drug use (2.8%) and a high prevalence of (OTC) drug self-medication (31.4%) and psychopathological symptoms (34.7%). Self-medication with OTC drugs independently and significantly predicted severities of insomnia (β = .178, p = .001), intellect disorder (β = .244, p = .000), heat dis-order ( β = .109, p = .046), mood disorder (β = .188, p = .001), head region disorder (β = .162, p = .003), alimentary tract disorder (β = .118, p = .030),general somatic disorder (β = .244, p = .000), and general psychopathology (β= .229, p = .000). The study reports a high prevalence of psychopathological symptoms among the Nigerian sample and concludes that the SM of OTC drugs is a significant predictor of the severity of the symptoms of psychopathology among pregnant women.
Keywords: Self-Medication; Over-the-counter drugs; Psychopathological symptoms; Pregnant women; Nigeria